# Prove the following:$( i).\ ( \frac{\cot ^{2} A}{(\operatorname{cosec} A+1)^{2}}=\frac{1-\sin A}{1+\sin A})$$( ii).\ \frac{1+\sin A}{\cos A}+\frac{\cos A}{1+\sin A}=2 \sec A)$.

Given:

$( i).\ ( \frac{\cot ^{2} A}{(\operatorname{cosec} A+1)^{2}}=\frac{1-\sin A}{1+\sin A})$

$( ii).\ \frac{1+\sin A}{\cos A}+\frac{\cos A}{1+\sin A}=2 \sec A)$.

To do: To prove the given expressions.

Solution:

$( i)$. L.H.S.$=\frac{cot ^{2} A}{( cosec A+1)^{2}}$

$=\frac{cosec^2A-1}{( \frac{1}{sin A}+1)^2}$         [$\because cot^2A=cosec^2A-1$]

$=\frac{\frac{1}{sin^2A}-1}{( \frac{1+sinA}{sinA})^2}$                 [$\because cosec^2A=\frac{1}{sin^2A}$]

$=\frac{\frac{1-sin^2A}{sin^2A}}{\frac{( 1+sinA)^2}{sin^2A}}$

$=\frac{1-sin^2A}{( 1+sinA)^2}$

$=\frac{( 1-sinA)( 1+sinA)}{( 1+sinA)^2}$

$=\frac{1-sinA}{1+sinA}$

$=R.H.S.$

Hence proved.

$( ii).$  LH.S.$= \frac{1+\sin A}{\cos A}+\frac{\cos A}{1+\sin A}=2 \sec A)$

$=\frac{( 1+sinA)^2+cos^2A}{cosA( 1+sinA)}$

$=\frac{1+sin^2A+2sinA+cos^2A}{cosA( 1+sinA)}$

$=\frac{1+( sin^2A+cos^2A)+2sinA}{cosA( 1+sinA)}$

$=\frac{1+1+2sinA}{cosA( 1+sinA)}$                  [$\because sin^2A+cos^2A=1$]

$=\frac{2+2sinA}{cosA( 1+sinA)}$

$=\frac{2( 1+sinA)}{cosA( 1+sinA)}$

$=\frac{2}{cosA}$

$=2secA$                    [$\because \frac{1}{cosA}=secA$]

$=R.H.S.$

Tutorialspoint

Simply Easy Learning

Updated on: 10-Oct-2022

39 Views